Changes in the advection of Antarctic Intermediate Water to the northern Chilean coast during the last 970 kyr. (1st October 2013) - Martínez‐Méndez, G.; Hebbeln, D.; Mohtadi, M.; Lamy, F.; De Pol‐Holz, R.; Reyes‐Macaya, D.; Freudenthal, T.
Abstract [1] The Antarctic Intermediate Water (AAIW) is a key player in global‐scale oceanic overturning processes and an important conduit for heat, fresh water, and carbon transport. The AAIW past variability is poorly understood mainly due to the lack of sedimentary archives at intermediate water depths. We present records of benthic stable isotopes from sediments retrieved with the seafloor drill rig MARUM‐MeBo at 956 m water depth off northern Chile (GeoB15016, 27°29.48′S, 71°07.58′W) that extend back to 970 ka. The sediments at this site are presently deposited at the boundary between AAIW and Pacific Deep Water (PDW). For previous peak interglacials, our results reveal similar benthic δ13C values at site GeoB15016 and of a newly generated stack of benthic δ13C from various deep Pacific cores representing the "average PDW." This suggests, unlike today, the absence of AAIW at the site and the presence of nearly pure PDW. In contrast, more positive δ13C values at site GeoB15016 compared to the stack imply a considerable AAIW contribution during cold phases of interglacials and especially during glacials. Besides, we used three short sediment cores to reconstruct benthic δ13C values from the AAIW core during the last glacial and found a δ13C signature similar to today's. Assuming that this was the case also for the past 970 kyr, we demonstrate that sea level changes and latitudinal migrations of the AAIW formation site can only account for about 50% of the full range of past δ13C increases at site GeoB15016 during cold periods. Other processes that could explain the remaining of the positive δ13C anomalies are increases in glacial AAIW production and/or deeper convection of the AAIW with respect to preceding interglacials.